STRATEGI BADAN AMIL ZAKAT NASIONAL (BAZNAS) DALAM MENINGKATKAN PENGUMPULAN ZAKAT, INFAK DAN SHADAQAH (ZIS) - Sabilla Khumaira; Ike Rachmawati; Tuah Nur (Jurnal Governansi, 2023)
This study aims to explore how the National Board of Zakat (BAZNAS) improves the collection of Zakat, Infaq and Shadaqah (ZIS) in Sukabumi Regency, and to identify factors that support or hinder the collection process. This research was triggered by the non-achievement of zakat, infaq, and shadaqah collection targets, as many people were unaware that BAZNAS had provided Zakat Collection Units (UPZ) in each sub-district, which resulted in their reluctance to pay zakat directly to BAZNAS. In order to understand this phenomenon, the research used a qualitative method with a descriptive approach, which allows researchers to explore the information actually found in the field. Data were collected through interviews, on-site observations, as well as through documentation and regulations relevant to the research problem. This research focuses on the strategy theory initiated by Dess and Miller (2003), which includes the dimensions of goals, policies, and plans. The research concluded that BAZNAS Sukabumi Regency has a goal to increase the collection of Zakat, Infaq and Shadaqah, although most people prefer to channel it directly to the beneficiaries (mustahiq). Therefore, the research suggests that it is necessary to re-optimize existing policies and design collection strategies that are more in line with the times to achieve the set goals.